The influence of FADS genetic variation and omega-3 fatty acid deficiency on cardiometabolic disease risk in a Mexican American population - Blomquist, Sarah A.; Albrecht, Jil H.; Hallmark, Brian; Klimentidis, Yann C.; Garcia, Luis A.; Mandarino, Lawrence J.; Coletta, Dawn K.; Chilton, Floyd H. (Frontiers in Nutrition, 2025)
BackgroundLatinos, the largest racial/ethnic minority group in the United States, have high rates of cardiometabolic diseases, hypothesized due in part to genetic variation in the fatty acid desaturase (FADS) cluster that is associated with reduced omega-3 (n-3) highly unsaturated fatty acid (HUFA) biosynthesis. This study examined how variations in FADS and other HUFA pathway-related genes (ELOVL5 and ELOVL2) impact cardiometabolic disease risk factors in Latinos of Mexican Ancestry (LMA).ResultsThis study analyzed 493 self-identified LMA from the Arizona Insulin Resistance registry (AIR) and found a marked enrichment in FADS alleles linked the ancestral haplotype (AH) compared to European Americans. LMA individuals with two AH alleles produced markedly lower levels of n-6 and n-3 HUFAs. However, this was more pronounced with the n-3 HUFAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), where the n-6 arachidonic acid (ARA) to EPA and DHA ratios were 30:1 and 5:1, respectively, and circulating EPA levels were reduced to <5 ng/mL. Importantly, genetic variations in both FADS and ELOVL2/5 regions also were strongly associated with several cardiometabolic disease (CMD) markers, with the presence of two FADS AH alleles corresponding to a 45, 33, and 41% increase in fasting insulin, triglyceride levels and HOMA-IR, respectively.ConclusionThis study reveals the potential impact of genetically influenced HUFA regulation and n-3 HUFA deficiency on cardiometabolic disease risk within LMA. These insights provide a strong rationale for future studies and clinical trials that focus on n-3 HUFA supplementation to mitigate CMD disparities in LMA populations.